2016
DOI: 10.1007/s00592-016-0955-9
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles of human iPSCs differentiation into insulin-producing cells

Abstract: We detected a specific hiPSCs microRNAs signature during differentiation into insulin-producing cells and demonstrated that differentially expressed microRNAs target several genes involved in pancreas organogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…Multiple studies have shown that miRNAs are pivotal regulators of different aspects of glucose homeostasis, such as peripheral insulin signaling [4], β cells function [5], and phenotype maintenance [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that miRNAs are pivotal regulators of different aspects of glucose homeostasis, such as peripheral insulin signaling [4], β cells function [5], and phenotype maintenance [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that miR-124a plays an important role in pancreatic endocrine development [13,37], insulin biosynthesis and secretion, and insulin signal transduction [12,15]. Despite these important biological roles, little is known about the regulation of miR-124 biogenesis in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Initially described as a brain-specific miRNA in mammals [9,10], MiR-124a-3p (miR-124a), is also well represented in the mouse pancreatic MIN6 β-cell line [11]. Increasing expression levels of miR-124a have been found during embryonic pancreas development [12] and differentiation of human induced pluripotent stem cells (hiPSCs) into insulin-producing cells [13], indicating its function in pancreatic β cell development. Emerging data suggest that miR-124a is overexpressed in pancreatic islets in humans with T2D compared to that in subjects without diabetes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…16 Pankreas farklılaşması esnasında insan uyarılmış pluripotent kök hücrelerinin insülin üreten hücrelere dönüşmesinde 18 farklı miRNA arasında sadece 347/768 miRNA'larının, belli bir zamanda tüm örneklerde ortak ekspresyon sergilediği bildirilmiştir. 49 Beta hücresine özgü çeşitli miRNA'ların diyabet öncesinde dolaşımda birikmesi, bu moleküllerin teşhiste önemli olabileceğini düşündürmektedir. Pankreas adacıklarında miRNA işlemlerinin düzenlenmesi diyabet durumunda değişmektedir.…”
Section: Di̇yabet Hastaliğinda Pankreati̇k Beta Hücresi̇ Ve Mirna'larunclassified